Emotional Intelligence: Mengapa EI Lebih Penting daripada IQ? - Silvia Damayanti; Masduki Asbari; Dani Setiawan; Muhammad Sayup Saputra (Yayasan Aya Sophia Indonesia, 2023)
This article is a critical reading of Daniel Goleman's inspiring and motivational guidebook